PENGGUNAAN DSS AHP, SAW DAN SMART UNTUK MENENTUKAN PRIORITAS PEMBANGUNAN DI KOTA MALANG - Deddy kusbianto; Purwoko Aji (SPIRIT, 2016)
Abstract: Economic growth has an important role in poverty reduction and job creation. During the five-year period of last economic growth on Malang City has increased, but when compared with Another City in East JavaMalang City economic growth not as a top grade. Edison added that he had been driving around Malang City. He considered if the potential in this City is big enough to use the community investing. Unfortunately, up to now,people are still not aware of the area with their potentials. In Malang, in conjunction with the issuance of Presidential Instruction No. 3 Year 2003 on National policies and strategies for the development of e-Government, has started the implementation of e-Government development through network building program "Cyber City" as the first step in the provision of telematics infrastructure is implemented in phases in annually starting fiscal year 2003. the level of the economy on average better than the other areas that immediately support the market mechanism in Malang City. New Malang culture today, shows significant progress because of its ability to adapt and adopt the material updates as other nations in the world (many high schools in poor cities now), a source of inspiration to compete fairly for the sake of increased revenueper capita Malang later in life.  And the variables that affect the increase in per capita income for the city of Malang is to have consecutive priorityas follows: the level of technology used, the social system and the attitude of the community, the number and quality of labor, capital goods available, and a wealth of resources nature and the land.Keywords: Income per capita, economic growth, Malang City